Development of a Science Module on Temperature and Heat Topics to Improve Critical Thinking and Collaboration Skills - Mohamad Nor Aufa; Sutarto Hadi; Syahmani Syahmani; Rusmansyah Rusmansyah; Muhammad Hasbie; Isnawati Isnawati (Universitas Lambung Mangkurat, 2021)
This study aims to produce a science module based on mobile-collaborative-based science learning (m-CBSL) with the topic of temperature and heat and describe the resulting module's validity and practicality. The research design was Educational Design Research (EDR). The data collection techniques used were literature study, walkthrough, interview, and questionnaire. The instrument used in this study was a questionnaire of validity and practicality. Data analysis techniques include descriptive data analysis, validation sheets, and questionnaires. Module validation sheets were given to 5 validators. In contrast, practicality sheets were given to 9 students of class VII SMP Negeri 12 Banjarmasin (small group) and 62 students and three science teachers at SMP Negeri 6 & 12 Banjarmasin field test. The validity questionnaire analysis results concluded that the validity of the module was 3.71